Customer participation in the customization of services: Effects on satisfaction and behavioral intentions - Lennart Straus; Thomas Robbert; Stefan Roth (jbm - Journal of Business Market Management, 2016)
Customers' evaluation of the service process has important implications for service providers. However, research on customer participation at the specification stage of a customization process and its effects on the evaluation of the process and service outcome is still scarce. This paper analyzes the effect of customer participation in a scenario experiment with two measurement points in which customers and salespeople collectively customize a service offering according to customers' needs. We find that customer participation has a positive impact on satisfaction and behavioral intentions irrespective of the actual service outcome. Even for negative service experiences, participating customers are significantly more satisfied than customers who played a rather passive role at the specification stage of the service process.
urn:nbn:de:0114-jbm-v9i1.1510
Keywords: 650; Customer Participation; Service Customization; Satisfaction